Pendampingan Lokakarya 1 Calon Guru Penggerak (CGP) Angkatan 9 Kabupaten Enrekang dalam Pemetaan Komunitas Praktisi - Aya, Ismaya Maya; Amiruddin, Eka Wahyuni; Ridwan, Madinatul Munawwarah; Chabir Galib, Andi Ahmad; suherman, Suherman (MALLOMO: Journal of Community Service, 2023)
Community service activities with the theme of mentoring activities for prospective mobilizing teacher workshops. The purpose of this activity is to provide assistance to Prospective Mover Teachers Batch 9 of Enrekang Regency in carrying out Workshop 1 activities. The implementation of activities using face-to-face (offline) methods for 1 day (8 JP) is located at SMP Negeri 1 Enrekang. The activity was attended by 18 Prospective Driving Teachers of Enrekang Regency. The result of this activity is that the Prospective Teacher Mobilizer understands that the community of practice is a forum to develop the competence of learning leaders in driving the education ecosystem.